Perceived Work Environment and the Occurrence of Accidents: A Study Based on Kuching Area of Sarawak - Li, Sa Lau; Talwar, Prashanth; Shahren Ahmad, Zaidi Adruce; Yin, Bee Oon (UNIMAS Publisher, 2016)
Perceived work environment could be described as the opinions and attitudes of workers towards their work condition. Elements of perceived work environment such as physical environment, supportive work environment, and perceived work tasks may possibly be important factors that influence the occurrence of accidents. The objective of this study is to examine the relationship between perceived work envi-ronment and the occurrence of accidents within an electronic manufacturing industry in Kuching, Sarawak. A cross-sectional survey utilizing a bilingual self-report ques-tionnaire was conducted to garner data from 50 workers. Independent t-test and Pear-son moment correlation were used to assess data. The results indicated that the occur-rence of accidents was not affected by age group. Although physical environment and perceived work tasks did not demonstrate significant relationships with the occur-rence of accidents, supportive work environment exhibited a significant inverse rela-tionship, thereby indicating that accidents could be lowered in the presence of higher supportive work environment. Thus, support and help from co-workers are essential determinants of safety at the workplace.